2020
DOI: 10.4049/jimmunol.2000419
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation of the Microbiome and Immune Response

Abstract: The evolution of the immune system, diet, and the microbiome are interconnected. Dietary metabolites modulate the cells of the immune system both directly and indirectly via shifts in the composition of the intestinal microbiota and its products. As a result, overconsumption and malnutrition can have substantial effects on immune responses and inflammation. In resource-rich nations, diets high in processed foods, fat, and sugar can contribute to chronic inflammatory conditions, which are on the rise worldwide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 152 publications
(148 reference statements)
0
17
0
Order By: Relevance
“…However, it is important to understand that these changes should not be ascribed to certain foods or macronutrients, but to the entire diet composition, along with a higher consumption of plant-based sources [ 168 , 169 ]. Thus, malnutrition in occidental countries contributes to a state of chronic inflammation and metabolic problems, whereas the typical undernourishment of underdeveloped countries leads to nutritional deficits, and therefore immunodeficiencies [ 170 ].…”
Section: Diet As the Main Modulator Between Gut Microbiota And Immmentioning
confidence: 99%
“…However, it is important to understand that these changes should not be ascribed to certain foods or macronutrients, but to the entire diet composition, along with a higher consumption of plant-based sources [ 168 , 169 ]. Thus, malnutrition in occidental countries contributes to a state of chronic inflammation and metabolic problems, whereas the typical undernourishment of underdeveloped countries leads to nutritional deficits, and therefore immunodeficiencies [ 170 ].…”
Section: Diet As the Main Modulator Between Gut Microbiota And Immmentioning
confidence: 99%
“…The human microbiome is the ecological system of commensal, symbiotic, and pathogenic microorganisms inhabiting our bodies [105]. Recent studies have shown that changes in microorganism species in the microbiome, despite many of them being commensal, contribute to host immune dysregulation and carcinogenesis [106][107][108][109]. Identification and exploration of the interplay between microorganisms and the human host may provide new insights to a novel treatment axis.…”
Section: Differential Contributions Of Oral Microbiome To Hpv+ and Hpv− Hnsccsmentioning
confidence: 99%
“…There is normal physiological mucosal turn over and shedding, intermittent luminal trauma from ingested food, loss of integrity of cell junctions which releases additional antigens. The immune cells constantly sample food antigens, pathobiont, such as other non-commensal bacteria, viruses and other foreign peptides [37,38]. The gut epithelium along with the immune cells produces protective factors, such as secretory IgA, α-Defensins, antimicrobial peptides and mucus.…”
Section: Gut Immune Systemmentioning
confidence: 99%